Predictors of Medication Adherence among Hypertensive Patients at the Parit Haji Husin II Public Health Center Pontianak - Zuhudan, Fahim; Syahab Assegaf, Syarifah Nurul Yanti Rizki; Nurmainah, Nurmainah (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2026)
Background: Hypertension remains highly prevalent, while medication adherence is still low at Parit H. Husin II Community Health Center, underscoring the importance of examining its associated factors.Methods: This analytical observational study used a cross-sectional design conducted at Parit H. Husin II Community Health Center, Southeast Pontianak, from December 2024 to January 2025. A total of 119 hypertensive patients were included. Data were collected using validated questionnaires, including the Morisky Medication Adherence Scale (MMAS-8) to assess medication adherence. Data were analyzed using univariate, Chi-square, and logistic regression tests.Result: The majority of respondents were female (61,3%), had higher education (52,1%), were unemployed (59,7%), had suffered from hypertension for less than 5 years (86,6%), had health insurance from BPJS (94,1%), had low knowledge of hypertension (52,9%), good access to health services (87,4%), high family support (63%), high support from health workers (74,8%), high motivation to seek treatment (63,9%), and adherence to antihypertensive medication (53,8%). The Chi-square test results showed a relationship between gender (p=0,218), education level (p=0,000), employment status (p=0,760), duration of hypertension (p=0,004), health insurance coverage (p=0,072), knowledge level (p=0,011), accessibility of health services (p=0,005), family support (p=0,611), role of health workers (p=0,366), motivation to seek treatment (p=0,002) with medication adherence. The results of the logistic regression test obtained the factor of duration of hypertension (OR=10,422).Conclusion: Length of time suffering from hypertension is the most influential factor on adherence to taking medication (p=0,020; OR=10,422).